SOUTH KOREAN GASTRODIPLOMACY: REFLECTION ON THE FILTRATION OF CONTEMPORARY THREATS TO INDONESIAN NATIONAL IDENTITY - Baihaqi, Abyan; Santoso, Puguh; Malik, Ichsan; Widodo, Pujo; Sukendro, Achmed (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This study examines contemporary civilization's evolution towards new patterns of interaction dominated by globalization and technology, as well as its impact on national defense. The research begins with the First Peace of Kappel, which introduced the notion that gastrodiplomacy could be a pathway to peace. The aim of this study is to analyze how gastrodiplomacy, as a manifestation of national identity, may pose a non-military threat to Indonesia's national defense, utilizing the Cultural Dimensions Theory approach. However, the research findings present a divergent perspective when considering the success of the Korean Wave as a new form of Asian-style Westernization, explained through the strategic approach of Multi-Track Diplomacy. The resulting acculturation phenomenon demonstrates significant influence as a novel diplomatic medium, thereby creating competition in the socio-cultural, economic, and ideological aspects of Indonesian society. Ultimately, it is crucial for Indonesia to play a role in gastrodiplomacy within the international order, as crystallized in Law Number 3 of 2003, particularly given Indonesia's diversity and wealth of national identity.